BFT-Dep: Automatic deployment of byzantine fault-tolerant services in PaaS cloud - Li, Bijun; Kapitza, Rüdiger (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2016)
Cloud computing has been a massive trend over the recent years and eased the deployment of scalable distributed applications. While initially renting out virtual machines was the predominant form of cloud computing, nowadays Platform as a Service (PaaS) solutions are emerging. The main advantages of the latter are a faster and easier application deployment as well as built-in support for horizontal scalability. However, when it comes to services with more demanding dependability requirements, currently provided deployment mechanisms quickly become insufficient, forcing cloud customers to fall back into manual, selfmade strategies. In this paper, we present BFT-Dep, a framework for deploying Byzantine fault-tolerant (BFT) services in a PaaS cloud automatically. BFT-Dep leverages the existing PaaS functionality to address specific deployment requirements and provides tailored support to set up and manage replicated services. It flexibly integrates BFT protocols as an independent service layer, thereby alleviating the complexity that the deployment of such systems entails. An initial prototype of BFT-Dep has been implemented on top of the open-source PaaS platform Open- Shift and a first evaluation shows its practicability.
CRIS-Team Scopus Importer:2022-07-19
Keywords: Automatic application deployment; Byzantine fault tolerance; Platform as a service (PaaS) cloud